Enthalpies of Combustion and Formation of Histidine Stereoisomers - A. Neacsu; D. Gheorghe; I. Contineanu; A. M. Sofronia; F. Teodorescu; S. Perişanu (Journal of Chemistry)
The combustion energy of histidine enantiomers (L and D) and of their racemic mixture was measured experimentally. The following values for the enthalpies of formation corresponding to the crystalline state were derived (L = −451.7, D = −448.7, DL = −451.5 kJ·mol−1), and information concerning their stability was obtained by correlating the values of the above thermochemical quantity with the structure of the molecules by using the group additivity scheme. The samples were characterized using a simultaneous thermogravimetry (TG) coupled with differential scanning calorimetry (DSC) techniques in the temperature range between ambient and beyond melting-decomposition, and the corresponding parameters were calculated. The high values of the decomposition temperatures highlight the stability of the compounds. The decomposition reactions are discussed in terms of DSC and TG data, obtained by us and other researchers.